(untitled) (Research, Society and Development, 2021)
Fetal mortality is a complication of pregnancy that can bring clinical, emotional and obstetric disorders to women, which can be disastrous with subsequent consequences that are often irreparable. Being considered an indicator of population health, denoting as the causes of interventions improvements in technological advances and in the quality of pre and perinatal care, even in risky situations. The objective was to highlight fetal deaths resulting from the various maternal influences experienced in complex and varied clinical situations that determine fetal development. The study was characterized by a survey of bibliographic data in scientific articles, magazines and textbooks, aiming to identify the variables that refer to perinatal mortality and health care for pregnant women and newborns, based on recommended basic recommendations. by scientific evidence, with emphasis on the causes arising from maternal factors and pregnancy complications. Thus, it is necessary that professionals are required to plan preventive actions in prenatal consultations so that possible cases with failures are avoidable in the perinatal care process.